The conflicts of child custody in Malaysia: sole custody vs. joint custody - Kamaruddin, Zaleha (s.n, 2012)
Generally, the law relating to custody and visitation rights after divorce advocates the best interests of the child as the main consideration and these interests are adopted through sole or joint custody. Recent sociological studies indicate that under sole custody, custody of the child is mostly awarded to the mother. It means that the mother obtains the residence of the child and parental responsibility as well as care for the child. Visitation rights are mostly awarded to the divorced father. The main problem arising from sole custody is the lack of contact between the child and the father. The other problem is child support obligation. Common cited reasons of these problems include parental remarriage, financial status, negligence, responsibility as well as care for the child, and geographical distance. Therefore, joint custody has been adopted by some countries in the name of legal reform to resolve these problems. This study discusses and analyses based on the Malaysian sample the patterns of the decisions of the civil and Shari’ah courts, experiences, and challenges faced by the divorced parents and the children regarding custody and visitation rights through the quantitative (1302 court cases) and qualitative (19 informants) methods. This study confirms patterns made by previous research which indicates the dominance of sole custody. Under sole custody, custody of the child is mostly awarded to the mother and visitation rights are mainly granted to the father. This study also identifies the main problem regarding the arrangements which is the lack of contact between the child and the father. Common reasons behind the problem include remarriage, financial status, and parental negligence. Interestingly, there is also the recognition of joint custody based on facts of the case. Apart from the custody and visitation rights after divorce arrangements, the residence of the child, visitation rights, and parental responsibility as well as care for the child are also considered. This study is relevant and important to policy makers and researchers working in similar areas.